The importance of the foot and ankle in athletic performance - LaPlaca, D. A.; Seedman, J. (Strength and Conditioning Journal, 2021)
Many strength and conditioning specialists prescribe exercises that use the major extensor muscles in the leg and thigh to help their athletes develop lower-body strength and power. Although this is important, an often neglected focus is specifically using and training the foot and ankle, which has shown to affect athletic performance. The purpose of this article is to: (a) provide the reader with researched information on how the foot and ankle impact athletic performance, and (b) provide practical applications for how to improve the function of the foot and ankle.